2009
DOI: 10.1186/1471-2202-10-87
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing microsurgical skills with EEG neurofeedback

Abstract: Background: By enabling individuals to self-regulate their brainwave activity in the field of optimal performance in healthy individuals, neurofeedback has been found to improve cognitive and artistic performance. Here we assessed whether two distinct EEG neurofeedback protocols could develop surgical skill, given the important role this skill plays in medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
112
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 41 publications
0
112
1
5
Order By: Relevance
“…No significant change in putting performance was observed in the control group. Previous studies have demonstrated that augmenting SMR by NFT improved visual motor performance (Ros et al, 2009) and increased self-rating scores of subjective flow state in dancers (Gruzelier et al, 2010). Furthermore, augmenting SMR by NFT was related to an improved attention-related mental state (Vernon et al, 2003) and memory performance (Hoedlmoser et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…No significant change in putting performance was observed in the control group. Previous studies have demonstrated that augmenting SMR by NFT improved visual motor performance (Ros et al, 2009) and increased self-rating scores of subjective flow state in dancers (Gruzelier et al, 2010). Furthermore, augmenting SMR by NFT was related to an improved attention-related mental state (Vernon et al, 2003) and memory performance (Hoedlmoser et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The drop in sensorimotor activity, as reflected by increased SMR power, may indicate a greater adaptive task-related attention allocation that facilitates the execution of sport performance (Gruzelier et al, 2010). Increasing SMR power through NFT is also related to more efficient and modulated visuomotor performance (Gruzelier et al, 2010;Ros et al, 2009). These results suggest that augmenting SMR power led to an improved adjustment of somatosensory and sensorimotor pathways (Kober et al, 2014), which resulted in increased task-related attention toward specific tasks (Egner & Gruzelier, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A modo de resumen, por no disponer de espacio en este lugar para examinar detenidamente los resultados de las investigaciones existentes sobre los mismos, presentamos a continuación en la tabla 1 un cuadro resumen de los distintos equipos técnicos de registros fisiológicos existentes y las principales respuestas fisiológicas que pueden ser registradas o medidas a través de los mismos (Arns, Ridder, Strehl, Bretelet y Coenen, 2009;Budzynski, Budzynski, Evans y Abarbanal, 2005;Coben y Evans, 2011;Kropotov, 2009;Larsen, 2012;Ros et al, 2009;Singer, 2004).…”
Section: Aplicaciones Clínicas Del Biofeedbackunclassified